Randomized controlled trial comparing 200 µg and 400 µg sublingual misoprostol for prevention of primary postpartum hemorrhage. (2016)
Objective: To compare efficacy and adverse effects of 200 μg and 400μgmisoprostol for prevention of postpartum hemorrhage (PPH). Methods: In a randomized control trial, women with term singleton pregnancies in active labor attending University College Hospital, Ibadan, Nigeria, were enrolled between July 2011 and February 2012. Participants were randomly assigned using random numbers (block size four) to receive 200 μg or 400 μg sublingual misoprostol after delivery of the anterior shoulder, alongside intravenous oxytocin. Investigators were masked to group assignment, but participants were not. The primary outcomes were blood loss up to 1 h after delivery, PPH (blood loss ≥500 mL), and adverse effects. Results: Overall, 62 patients were assigned to each group. No significant differences between the 200-μg and 400-μg groups were recorded in mean per partum blood loss (307 ± 145 mL vs 296 ± 151 mL; P =0.679) and PPH occurrence (5 [8.1%] vs 6 [9.7%] women; P=0.752). Noticeable adverse effects were reported by 16 (25.8%) women in the 200-μg group and 42 (67.7%) in the 400-μg group (P b 0.001). Risk of shivering was significantly lower with 200 μg than 400 μg (relative risk 0.33, 95% confidence interval 0.19–0.58). Conclusion: Blood loss and PPH occurrence did not differ by misoprostol dose, but a 200-μg dose was associated with a reduction in adverse effects.